Corticostriatal dynamics underlying components of binge-like consumption of palatable food in mice. (1st April 2023) - Hildebrandt, Britny A.; Fisher, Hayley; LaPalombara, Zoe; Young, Michael E.; Ahmari, Susanne E.
Abstract: Binge eating (BE) is a maladaptive repetitive feeding behavior present across nearly all eating disorder diagnoses. Despite the substantial negative impact of BE on psychological and physiological health, its underlying neural mechanisms are largely unknown. Other repetitive behavior disorders (e.g., obsessive compulsive disorder) show dysfunction within corticostriatal circuitry. However, to date, no work has investigated the in vivo neural dynamics underlying corticostriatal activity during BE episodes. The aim of the current study was to longitudinally examine in vivo neural activity within corticostriatal regions – the infralimbic cortex (IL) and dorsolateral striatum (DLS)– in a robust pre-clinical model for BE. Female C57BL6/J mice (N = 32) were randomized to receive: 1) intermittent (daily, 2-h) binge-like access to palatable food (sweetened condensed milk) (BE), or 2) continuous, non-intermittent (24-h) access to palatable food (control). In vivo calcium imaging was performed via fiber photometry at baseline and after chronic (4 weeks) engagement in the model for BE. Specific consummatory behaviors (feeding bout onset/offset) during recordings were captured using lickometers which generated TTL outputs for precise alignment of behavior to neural data. IL showed no specific changes in neural activity related to BE. However, BE animals showed decreased DLS activity at feeding onset and offset at the chronic timepoint when compared to activity at the baseline timepoint. Additionally, BE mice had significantly lower DLS activity at feeding onset and offset at the chronic timepoint compared to control mice. These results point to a role for DLS hypofunction in chronic BE, highlighting a potential target for future treatment intervention.